Maximizing the Productivity of Olives by Using Some Materials and Its Impacts on the Quality Indices of Picual Olive Oil - Arafat, Shaker M; EL-Sayed, Mohamed E (Journal of Food Technology Research, 2014)
The objective of this work was study that the effect using one treatment of (Girdling at first week of January and Kaolin sprayed at rate 5% mid December) and chemical (Calcium carbonate, sprayed at rate 5% mid December, Naphthalene acetic acid at 100ppm mid December and Boric acid (17.50%) at 300ppm in first week of March) on oil yield, quality indices, minor components and fatty acids composition of olive Picual cv. during seasons 2012-2013. Yield/tree, fruit weight, seed weight, flesh weight, flesh/fruit weight, flesh/stone, moisture and oil contents (%) were determined. Quality indices (acid value, peroxide value, absorbance at K232nm, K270 nm and ∆k, value), sensory evaluation, total polyphenol, tocopherol, bitter index at K225, pigments content, oxidative stability and Fatty acid composition were determined. Results indicated that the treated tree (Picual cv.) by Girdling, Boric acid, Naphthalene acetic acid and Kaolin gave a higher content in oil percentage/tree. Also, same the treatments gave best values in quality indices, total polyphenol, tocopherol and oxidative stability compared with untreated and treated samples with calcium carbonate. On the other hand, the treated trees by Girdling, Boric acid, Naphthalene acetic acid and Kaolin surpassed on untreated and treated samples with calcium carbonate in oleic acid levels. Generally, can be used (Girdling, Boric acid, Naphthalene acetic acid and Kaolin) to increase the productivity of olive trees Picual cv. and also improve the quality attributes of the oil extracted. Also these treatments increased the oleic acid more than untreated sample.